A study of clinical and serological correlation of early myocardial injury in elderly patients infected with the Omicron variant - Yu, Xueying; Li, Xiaoguang; Xia, Shuai; Lu, Lu; Fan, Jiahui; Wang, Ying; Fu, Yan; Suo, Chen; Man, Qiuhong; Xiong, Lize (Frontiers in Cardiovascular Medicine, 2024)
This study aims to elucidate the clinical characteristics and potential risk factors associated with myocardial injury in aging patients within the age range of 60 years and above infected with the Omicron variant. Myocardial injury was defined by elevated cardiac troponin concentrations surpassing the 99th percentile upper reference limit.Among 772 aging Omicron-infected patients, categorized into myocardial injury (n=263) and non-myocardial injury (n=509) groups, the occurrence rate of myocardial injury was 34.07%. Patients with myocardial injury were found to have a significantly higher likelihood of requiring intensive care (P<0.05). Comparing myocardial injury patients with non-myocardial injury patients, notable differences were observed in age, pre-existing medical conditions (e.g., hypertension, coronary heart disease, cerebrovascular disease, arrhythmia, chronic kidney disease, and heart failure), and various laboratory biomarkers, including cycle threshold-ORF1ab gene (Ct-ORF1ab), cycle threshold-N gene (Ct-N), white blood cell (WBC), neutrophil (NEUT), NEUT%, lymphocyte (LYM), LYM%, D-dimer, interleukin-6, procalcitonin, c-reactive protein (CRP), serum amyloid A (SAA), total protein (TP), lactate dehydrogenase (LDH), aspartate aminotransferase (ALT), glomerular filtration rate (eGFR), blood urea nitrogen (BUN), and serum creatinine (sCr) (P<0.05). Furthermore, employing multivariable logistic regression, we identified several potential risk factors for myocardial injury in Omicron variant-infected aging patients, such as advanced age, pre-existing coronary artery disease, interleukin-6>22.69 pg/mL, procalcitonin>0.0435 ng/mL, D-dimer>0.615 mg/L, and sCr>81.30 umol/L. Our findings offer valuable insights into the clinical characteristics and potential risk factors associated with myocardial injury in aging patients infected with the SARS-CoV-2 Omicron variant. This knowledge serves as a critical reference for early diagnosis and timely clinical intervention.